2004
DOI: 10.1073/pnas.0404332101
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of RuvAB-catalyzed branch migration of single Holliday junctions

Abstract: authors of both papers note the following. ''In both articles, the branch migration activity of the molecular motor RuvAB on single Holliday junction structures was measured by the same micromanipulation technique. Surprisingly, the results found by each group concerning the nominal enzyme kinetics seem to differ by a factor of 2 (98 bp͞s and 43 bp͞s).''In fact this discrepancy is only apparent: it results from the use of different conventions for the definition of the speed of strand exchange. Indeed, without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…3 and Movie 3, which is published as supporting information on the PNAS web site). A similar result was obtained by Stavans and colleagues (15), although their detection system monitored DNA length. Our observation supports the suggestion that pauses are caused by the dissociation of the RuvB motors or the RuvA-RuvB complex from the junction and that resumption of branch migration in either direction corresponds to the equal probabilities of reassembly of RuvB hexamers or the RuvA-RuvB complex on the two alternative sets of branches.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…3 and Movie 3, which is published as supporting information on the PNAS web site). A similar result was obtained by Stavans and colleagues (15), although their detection system monitored DNA length. Our observation supports the suggestion that pauses are caused by the dissociation of the RuvB motors or the RuvA-RuvB complex from the junction and that resumption of branch migration in either direction corresponds to the equal probabilities of reassembly of RuvB hexamers or the RuvA-RuvB complex on the two alternative sets of branches.…”
Section: Resultssupporting
confidence: 69%
“…Recently, RuvA-RuvB-mediated Holliday junction branch migration was visualized by single-molecule analyses (13)(14)(15). The branch migration rates were measured by monitoring the height of tethered beads.…”
mentioning
confidence: 99%
“…Previously it has been reported from different systems that RuvB proteins are involved in the holliday junction formation, branch migration and resolution of holliday junction [5][6][7]. Further studies on RuvBs confirmed their involvement in multiple cellular pathways such as cell cycle progression and RNA polymerase IIdirected transcription [8], DNA damage response, replication fork reversal [9], nonsense-mediated mRNA decay [10], insulin stimulated GLUT4 translocation [11], small nucleolar ribonucleotide protein (snoRNPs) assembly [12], cellular transformation, cancer metastasis, apoptosis, mitosis, and development [13,14].…”
mentioning
confidence: 99%
“…Although protein-mediated branch migration has been studied extensively for various enzymes (20)(21)(22) and recently at the singlemolecule level for RuvAB (23)(24)(25), the mechanics of spontaneous migration remain largely unknown. Ensemble measurements of spontaneous branch migration in homologous junctions have detected a 1,000-fold decrease in the migration rate upon the addition of Mg 2ϩ (26,27).…”
mentioning
confidence: 99%